TINJAUAN YURIDIS MENGENAI PEMBERIAN GRASI BAGI TERPIDANA MATI - Dedi Gultom, Josi; Oka Parwata, A. A. Gde (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013)
Clemency is an effort that may be filed by death row inmate to the President to ask for forgiveness or reduction of sentence to the President in order to avoid the implementation of the death penalty. In other words clemency was sentenced to death early efforts to preserve his life. By granting clemency to death row inmate is President authority as stipulated in the 1945 Constitution Article 14 paragraph (1) and the Act No. 5 of 2010 on the Amendment to the Law No. 22 Year 2002 on clemency.
Keywords: Clemency, Sentenced to Death, Death Penalty, President Act No. 5 of 2010 on the Amendment to the Law No. 22 Year 2002 on Clemency